TINJAUAN TERHADAP PEMIDANAAN ANAK BERKAITAN DENGAN TINDAK PIDANA PERSETUBUHAN BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Fajar Jaya (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT          The overview of juvenile punishment which related to a copulation crime based on Ordinance Number 35 of 2014 about Children Protection. It is advised by Mrs. Kunti Widayati, SH, M.Hum. as Adviser Lecturer I and Mrs. Ony Rosifany, SH, M.Hum. as Adviser Lecturer II.This research is formulating a problem about the application of juvenile punishment and motive factors for juvenile who commits a copulation crime. The aim of this scientific research is to develop the law science, especially to improve the knowledge and reference of the juvenile punishment application.This research method is using a normative juridical and empirical juridical method. Normative juridical method uses literature of law resource, empirical juridical method uses field research and interview.The description of this research describes the formulation a problem about the application of juvenile punishment juvenile who commits a copulation crime and participation of  law institution to rule the regulation as good as possible.According to the result of this research can be found there are many factors which influence a juvenile commits a copulation crime, especially internal factor which consist of psychis, mental and religion. And also external factor which consist of family, social, educational environment, and mass media. And the active role of society, especially law enforcement officials in handling cases of criminal offenses committed by children intercourse. Keywords :criminal, children, capulation